Macroprudential Solvency Stress Testing of the Insurance Sector - Jobst, Andreas A.; Broszeit, Timo.; Sugimoto, Nobuyasu (Washington, D.C. : International Monetary Fund, 2014)
Over the last decade, stress testing has become a central aspect of the Fund's bilateral and multilateral surveillance work. Recently, more emphasis has also been placed on the role of insurance for financial stability analysis. This paper reviews the current state of system-wide solvency stress tests for insurance based on a comparative review of national practices and the experiences from Fund's FSAP program with the aim of providing practical guidelines for the coherent and consistent implementation of such exercises. The paper also offers recommendations on improving the current insurance stress testing approaches and presentation of results.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet